Analysis of stress and smoking behavior among medical students in Jember University - Ramadhanti, Rizka Savira; Kusumastuti, Inke; Aziz, Ayu Munawaroh (Universitas Wijaya Kusuma Surabaya, 2026)
Background: Prolonged stress commonly induces specific coping strategies, including the adaptive problem-focused and the less adaptive emotion-focused coping. One example of emotion-focused coping is smoking. Objective: This study aimed to characterize the stress experienced by medical students and how they correlate with smoking behaviors. Methods: This descriptive research employed the Depression, Anxiety, Stress Scale – Stress Domain (DASS-S) and Silvan-Tomkin’s smoking behavior questionnaires as guides for semi-structured interviews. Five all-male medical students aged 19-22 years who were regular smokers were interviewed. Result: One respondent admitted the presence of significant stress. Despite the absence of significant stress, other respondents admitted occasional tension due to academic stressors. Two respondents associated smoking with obtaining positive emotions, while three associated smoking with coping with negative emotions. Conclusion: There is no clear correlation between stress and smoking behavior Future research might benefit from obtaining data from a larger sample number and considering the timing of the occurrence of stress when inquiring about smoking behavior to better establish the characteristics of stress and its correlations with smoking behavior.